The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.celrep.2020.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Germline Features Associated with Immune Infiltration in Solid Tumors

Abstract: Highlights d Tumor immune infiltration impacts response to immunotherapy d GWAS identifies inherited genetic variants associated with immune infiltration d Aggregating variants into genes and networks increases power to find associations d Germline associations may offer insight into predictors of response to immunotherapy

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 99 publications
0
32
0
Order By: Relevance
“…The JAK-STAT signaling pathway plays critical roles in cytokine receptors and can modulate the polarization of T helper cells. A recent report by Shahamatdar et al 46 analyzing germline variants in the TCGA cohort demonstrated that host genetics are associated with phenotypes that describe the immune component of the tumor microenvironment; they found one SNP associated with the amount of infiltrating follicular helper T cells; and 23 candidate genes, some of which are involved in cytokine-mediated signaling. Our patient cohort supports prior findings that patients with greater TCR richness in the peripheral blood had improved survival compared with patients with less clonal richness 47-49 .…”
Section: Discussionmentioning
confidence: 99%
“…The JAK-STAT signaling pathway plays critical roles in cytokine receptors and can modulate the polarization of T helper cells. A recent report by Shahamatdar et al 46 analyzing germline variants in the TCGA cohort demonstrated that host genetics are associated with phenotypes that describe the immune component of the tumor microenvironment; they found one SNP associated with the amount of infiltrating follicular helper T cells; and 23 candidate genes, some of which are involved in cytokine-mediated signaling. Our patient cohort supports prior findings that patients with greater TCR richness in the peripheral blood had improved survival compared with patients with less clonal richness 47-49 .…”
Section: Discussionmentioning
confidence: 99%
“…TME and TMB are two tumor characteristics important in immunotherapy response and prognosis. Recent studies have shown that germline variants can shape certain immune features within the TME of solid tumors [34][35][36] . Consistent with and complementary to these observations, our results show that the personal germline RDV load of a patient can impact their TME (see Supplementary Figure S4, Supplementary Table S11).…”
Section: Discussionmentioning
confidence: 99%
“…Next, in light of recent findings on the impact of germline variants on tumor immune microenvironment (TME) in various cancers [34][35][36] , we tested the association of increased germline RDV load in CPD, DDR, SCD and FA gene-sets with TME immune cell fractions. Briefly, to avoid any potential biases from B-cell immune signatures in blood cancers, we focused on 6,277 participants with solid tumors in TCGA by excluding 94 TCGA participants with hematological malignancies.…”
Section: Data-driven Analysis Of 17810 Gene-sets In Msigdb Again Identified Rdv Burden Inmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 15, 2021. ; https://doi.org/10.1101/2021.04.14.436660 doi: bioRxiv preprint immune infiltration levels and immune pathways, such as TGF-β and IFN-ɣ 9,10,23 . eGenes (genes with significant cis-eQTLs) in the TCGA are enriched for immune-related genes and associated with immune cell abundance within the tumor immune microenvironment (TIME) 24 .…”
Section: Efforts To Identify Germline Variation Influencing Anti-tumor Immune Responses Have Pointed To Effects Onmentioning
confidence: 99%
“…Germline variation is responsible for a considerable proportion of variation in immune traits in healthy populations 7,8 . In the context of tumors, germline variants have the potential to influence immune infiltration, antigen presentation and immunotherapy responses 9,10 . Autoimmune germline variants modify ICB response and variants underlying leukocyte genes predict tumor recurrence in breast cancer patients 11,12 .…”
Section: Introductionmentioning
confidence: 99%